2015
DOI: 10.1038/srep08927
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Next-generation Sequencing Reveals Novel EYS Mutations in Chinese Families with Autosomal Recessive Retinitis Pigmentosa

Abstract: EYS mutations demonstrate great genotypic and phenotypic varieties, and are one of the major causes for patients with autosomal recessive retinitis pigmentosa (ARRP). Here, we aim to determine the genetic lesions with phenotypic correlations in two Chinese families with ARRP. Medical histories and ophthalmic documentations were obtained from all participants from the two pedigrees. Targeted next-generation sequencing (NGS) on 189 genes was performed to screen for RP causative mutations in the two families. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 29 publications
(46 reference statements)
3
24
0
Order By: Relevance
“…Missense mutations were underrepresented in this study’s cohort, with only one missense mutation identified involving a single patient (P14). This patient was homozygous for a recurrent mutation c.6416G>A (p.(Cys2139Tyr)) that results in the formation of a hydrogen bond and the disappearance of a twist in the tertiary structure of the protein [ 59 ]. Pathogenicity of missense mutations is difficult to establish since tolerability depends on the location and the specific change.…”
Section: Discussionmentioning
confidence: 99%
“…Missense mutations were underrepresented in this study’s cohort, with only one missense mutation identified involving a single patient (P14). This patient was homozygous for a recurrent mutation c.6416G>A (p.(Cys2139Tyr)) that results in the formation of a hydrogen bond and the disappearance of a twist in the tertiary structure of the protein [ 59 ]. Pathogenicity of missense mutations is difficult to establish since tolerability depends on the location and the specific change.…”
Section: Discussionmentioning
confidence: 99%
“…In total, we collected information of 377 RP patients described in 43 papers (Abd El‐Aziz et al., ; Abd El‐Aziz et al., ; Abu‐Safieh et al., ; Arai et al., ; Audo et al., ; Audo et al., ; Bandah‐Rozenfeld et al., ; Barragan et al., ; Beryozkin et al., ; Bonilha et al., ; Chen, et al., ; Collin et al., ; Consugar et al., ; Di et al., ; Eisenberger et al., ; Ge et al., ; Glockle et al., ; Gonzalez‐del Pozo et al., ; Gu, Tian, Chen, & Zhao, ; Habibi, et al., ; Haer‐Wigman et al., ; Hashmi, et al., ; Hosono et al., ; Huang et al., ; Huang et al., ; Iwanami, Oshikawa, Nishida, Nakadomari, & Kato, ; Jinda et al., ; Kastner et al., ; Katagiri et al., ; Khan et al., ; Littink et al., ; Littink et al., ; Neveling et al., ; Nishiguchi et al., ; Oishi et al., ; O'Sullivan et al., ; Perez‐Carro et al., ; Pieras et al., ; Pierrottet et al., ; Siemiatkowska et al., ; Suto et al., ; Xu, et al., ; Yoon et al., ), in which 630 alleles with EYS variants were reported. In addition, we identified 26 novel variants found in 36 index patients that were not published previously (Table ).…”
Section: Eys Variantsmentioning
confidence: 99%
“…The autosomal recessive retinitis pigmentosa 25 (RP25, OMIM #612424) is caused by abnormal EYS (Abd El-Aziz et al, 2008; Collin et al, 2008), a secreted extracellular matrix protein, in several populations worldwide (Abd El-Aziz et al, 2008, 2010; Audo et al, 2010; Bandah-Rozenfeld et al, 2010; Barragán et al, 2010; Chen et al, 2015; Collin et al, 2008; Di et al, 2016; Hosono et al, 2012; Littink et al, 2010b). Mutations in EYS account for 5-16% of all autosomal recessive cases in Europe (Audo et al, 2010; Barragán et al, 2010; Littink et al, 2010b) and the most prevalent form of inherited retinal dystrophy in Japan (Arai et al, 2015; Iwanami et al, 2012).…”
Section: Introductionmentioning
confidence: 99%